2011
DOI: 10.1021/jp205107u
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Behavior of Completely Siliceous Zeolite ZSM-5 under High External Pressures

Abstract: The behavior of completely siliceous zeolite ZSM-5 (Si-ZSM-5) under high pressures up to 16 GPa were investigated by in situ Raman spectroscopy and X-ray diffraction with synchrotron radiation in a diamond anvil cell. Pressure-induced amorphization was observed in both as-made and calcined Si-ZSM-5, which transform to a low-density amorphous silica first and then to a high-density amorphous silica. However, transition pressures and reversibility were different for as-made and calcined Si-ZSM-5. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
18
1
Order By: Relevance
“…The similar structure flexibility to its anhydrous analogue in non-penetrating PTM indicates that the hydrated AlPO 4 -17 becomes more compressible as the pressure increased and that, as in the dehydrated phase, exhibits an elastic instability. Such behavior is the opposite to the structural changes as a function of pressure observed in other zeolites, which exhibit pressure-induced stiffening of the structure [22,23,24]. As evidenced by the evolution of the relative volume with pressure, there are at least four pressure ranges with different compressibility values before completely amorphization, and from which the three first, up to 3.2 GPa, seems to present pressure-induced softening, which decreases as the pressure increases.…”
Section: Discussionmentioning
confidence: 90%
“…The similar structure flexibility to its anhydrous analogue in non-penetrating PTM indicates that the hydrated AlPO 4 -17 becomes more compressible as the pressure increased and that, as in the dehydrated phase, exhibits an elastic instability. Such behavior is the opposite to the structural changes as a function of pressure observed in other zeolites, which exhibit pressure-induced stiffening of the structure [22,23,24]. As evidenced by the evolution of the relative volume with pressure, there are at least four pressure ranges with different compressibility values before completely amorphization, and from which the three first, up to 3.2 GPa, seems to present pressure-induced softening, which decreases as the pressure increases.…”
Section: Discussionmentioning
confidence: 90%
“…The solvent molecules occluded in the channels of as-made framework are believed to play ak ey role in restoring the structure and crystallinity of the framework when the pressure was released. Previouss tudies on as-made ZSM-5 [21] under high pressure showedt hat the interaction between the template molecules and zeolite framework preserves the local structures associated with the originalt opology at high pressure and, on releasing the pressure, the template redirects the silicate speciest op artially reform the initial topology.F or the as-made framework of MIL-68(In), the DMF solvent molecules may play as imilarr ole to that of template molecules in ZSM-5.F or the activated framework, the weakening and soft behavior of OH modes is associated with the formationo fh ydrogen bonds between the adjacent In-O octahedra in the framework. The OH modes are not recoveredo nc omplete decompression, as the empty framework is partially modified duringc ompression.T he existence of solvent molecules is thus clearlyp ivotal to the reversibility of the framework.…”
Section: Discussionmentioning
confidence: 98%
“…The solvent molecules occluded in the channels of as‐made framework are believed to play a key role in restoring the structure and crystallinity of the framework when the pressure was released. Previous studies on as‐made ZSM‐521 under high pressure showed that the interaction between the template molecules and zeolite framework preserves the local structures associated with the original topology at high pressure and, on releasing the pressure, the template redirects the silicate species to partially reform the initial topology. For the as‐made framework of MIL‐68(In), the DMF solvent molecules may play a similar role to that of template molecules in ZSM‐5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the incorporated molecules on PIA is also discussed by Fu et al (2012), who studied the PIA process of as-made (with template molecules occluded in the zeolite) and calcined Si-pure ZSM-5 by in situ Raman spectroscopy and X-ray diffraction, without PTM. These authors demonstrated that, although both phases undergo PIA, their amorphization threshold pressures are different.…”
Section: Pressure-induced Amorphizationmentioning
confidence: 99%